A Comparison of Blood Pathogen Detection Among Droplet Digital PCR, Metagenomic Next-Generation Sequencing, and Blood Culture in Critically Ill Patients With Suspected Bloodstream Infections - Hu, Bangchuan; Tao, Yue; Shao, Ziqiang; Zheng, Yang; Zhang, Run; Yang, Xuejing; Liu, Jingquan; Li, Xi; Sun, Renhua (Frontiers in Microbiology, 2021)
Metagenomic next generation sequencing (mNGS) and droplet digital PCR (ddPCR) have recently demonstrated great potential as an attractive diagnostic modality in detection of blood pathogens. However, few studies had compared these molecular based methods as applied in identification of bloodstream infections (BSIs). The prospective study was conducted in critically ill patients with suspected BSIs. Upon suspicion of BSIs, the whole blood samples were simultaneously drawn for ddPCR covering target detection of 20 common pathogens and 4 antimicrobial resistance (AMR) genes, mNGS, and blood culture, respectively. A head-to-head comparison was performed between ddPCR and mNGS. A total of 60 episodes of suspected BSIs was investigated in 45 critically ill patients, and ddPCR was positive in 50 (83.3%), mNGS in 41 (68.3%, not including viruses), and blood culture in 10 (16.7%) episodes. Compared with blood culture, both mNGS and ddPCR methods had a sensitivity of 90% (9/10). The head-head comparison showed that the ddPCR was more rapid ( 4 hours vs 2 days) and sensitive (88 vs 53 positive pathogens) than mNGS within the detection range of ddPCR, while mNGS could detect a broader range of pathogens than ddPCR. In addition, a total of 17 AMR genes including 14 blaKPC and 3 mecA were exclusively identified by ddPCR. Based on their respective limitations and strengths, the ddPCR method should be used for the earlier detection of common pathogens as well as ARM genes in suspected BSI patients, whereas the mNGS testing would be more appropriate for diagnosis of complicated BSIs.